Perlindungan Hukum Kreditur Atas Wanprestasi Perjanjian Kredit - Nelly, Roos (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The debtor who has made and also agreed to an agreement made jointly with the creditor in the case of the debtor requires a sum of money due in a credit agreement, the debtor often commits an act of default in the form of non-payment of the debt and as if the promise was not fulfilled. made collateral to another party and has been foreclosed, where the agreement must remain in force, requiring legal protection for creditors who have no collateral binding. Legal protection of creditors is regulated in the Book of the Civil Code. This study aims to provide creditors with an understanding of how forms of legal protection relate to collateral foreclosed by other parties either before or after the agreement is made. The type of research used is normative research, such as the use of books, discussion of theories and prevailing laws. In conclusion, this study is felt to be crucial to provide justice to those who need it.